Hydroxy nitrate production in the OH-initiated oxidation of alkenes - A. P. Teng; J. D. Crounse; L. Lee; J. M. St. Clair; R. C. Cohen; P. O. Wennberg (Atmospheric Chemistry and Physics, 2015)
Alkenes are oxidized rapidly in the atmosphere by addition of OH and subsequently O2 leading to the formation of β-hydroxy peroxy radicals. These peroxy radicals react with NO to form β-hydroxy nitrates with a branching ratio α. We quantify α for C2–C8 alkenes at 295 K ± 3 and 993 hPa. The branching ratio can be expressed as α = (0.045 ± 0.016) × N − (0.11 ± 0.05) where N is the number of heavy atoms (excluding the peroxy moiety), and listed errors are 2σ. These branching ratios are larger than previously reported and are similar to those for peroxy radicals formed from H abstraction from alkanes. We find the isomer distributions of β-hydroxy nitrates formed under NO-dominated peroxy radical chemistry to be different than the isomer distribution of hydroxy hydroperoxides produced under HO2-dominated peroxy radical chemistry. Assuming unity yield for the hydroperoxides implies that the branching ratio to form β-hydroxy nitrates increases with substitution of RO2. Deuterium substitution enhances the branching ratio to form hydroxy nitrates in both propene and isoprene by a factor of ~ 1.5. The role of alkene chemistry in the Houston region is re-evaluated using the RONO2 branching ratios reported here. Small alkenes are found to play a significant role in present-day oxidant formation more than a decade (2013) after the 2000 Texas Air Quality Study identified these compounds as major contributors to photochemical smog in Houston.